Pengaruh Positif Fenomena K-Pop Terhadap Karakter Generasi Muda di Indonesia - Regina Nurul Sakinah; Syofiyah Hasna; Yona Wahyuningsih (Departement of Mathematics Education, 2022)
Along with the development of technology in the era of globalization, people can access information very easily. One of them is access to the growing world of K-pop. Korean cultural products include film, music, drama, fashion, lifestyle, and industrial products. It has begun to color the lives of people in various parts of the world, especially in Indonesia. Indonesia is one of the countries that is the main target for the spread of Korean culture. The continuous spread of Korean culture encourages a love of Korean culture, and subsequently the formation of Korean culture in Indonesia. This study aims to determine the positive impact of Korean popular culture on the habits of the younger generation in Indonesia. The research method used is a qualitative approach with literature study and using descriptive methods. The data in this study were collected from the results of library research from journals and articles. The improvement of the development of this wave newspaper really needs to be discussed and must be considered by parents in seeing the character of their children. In this journal the author discusses the factors that cause the younger generation to like K-Pop and the positive impact of this K-Pop development on the character of the younger generation in Indonesia.